Private governance of public school: Representation, priorities, and compliance in New Orleans Charter School Boards - Lay, J. Celeste; Bauman, Anna (Urban Affairs Review)
In many cities, charter schools make up an increasing proportion of public schools, substantially altering education governance. In New Orleans, nearly every public school student attends a charter school. Each charter school or network has its own private governing board responsible for obtaining and maintaining the school$1 (Bs charter, school finances, and hiring school leadership. We know relatively little about the composition, priorities, or effectiveness of these boards. In this article, we find that New Orleans$1 (Bs charter boards are unrepresentative, are focused on fiduciary responsibilities rather than academics, and routinely fail to comply with state transparency laws. As more schools and other public services in urban areas move to private governance, it is important to examine the people who compose the boards, their decision-making processes, and the extent of public involvement. New Orleans provides a cautionary tale of how this governance system could operate in other cities with growing charter sectors. - Reproduced.s